2019
DOI: 10.1002/iub.2050
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA‐138 induces cell survival and reduces WNT/β‐catenin signaling of osteoarthritis chondrocytes through NEK2

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by joint pain, stiffness, and function degeneration with high incidence. Recent studies have been inspired based on the association between microRNAs (miRs) and therapeutic research of OA. Hence, the present study evaluates the effects of miR‐138 on chondrocyte proliferation, differentiation, and apoptosis through the WNT/β‐catenin signaling pathway in mice with OA by binding to NIMA‐related kinase 2 (NEK2). Appropriate dataset was selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We further hypothesize that the effect of mechanical loading or, specifically, of HP on Wnt/β-catenin pathway could be mediated by miRNA. Indeed, several investigations demonstrated, in human and rat OA chondrocyte cultures, the direct targeting of some miRNA, implicated in OA damage, on Wnt or β-catenin proteins [70][71][72][73]. Likewise, our data reported a reduced β-catenin protein expression when OA chondrocytes were transiently silenced with miR-34a specific inhibitor; moreover, miRNA inhibition limited the negative effects of overloading HP on β-catenin expression and enhanced, even if not significantly, those of low cyclic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…We further hypothesize that the effect of mechanical loading or, specifically, of HP on Wnt/β-catenin pathway could be mediated by miRNA. Indeed, several investigations demonstrated, in human and rat OA chondrocyte cultures, the direct targeting of some miRNA, implicated in OA damage, on Wnt or β-catenin proteins [70][71][72][73]. Likewise, our data reported a reduced β-catenin protein expression when OA chondrocytes were transiently silenced with miR-34a specific inhibitor; moreover, miRNA inhibition limited the negative effects of overloading HP on β-catenin expression and enhanced, even if not significantly, those of low cyclic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous signaling pathways are involved in the process of OA, including bone morphogenetic proteins (8), Indian hedgehog (9), hypoxia-induced and Wnt signaling pathways (10,11). As an important component of the Wnt signaling pathway, β-catenin is activated by Wnt family proteins and participates in the pathological process of KOA (12).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that miRs are vital for maintaining cartilage homeostasis and developing cartilage destruction 14,15 . Evidence obtained in vivo and in vitro reveals that miR‐24, miR‐93‐5p and miR‐138 promote chondrocyte survival and attenuate cartilage degradation in OA via repressing their downstream targets 16–18 . Inversely, overexpression of miR‐495 may be linked with chondrocyte apoptosis by regulating chemokine ligand 4 in OA 14 .…”
Section: Introductionmentioning
confidence: 99%